2013
DOI: 10.1007/s13312-013-0168-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of patients with gross hypotonia and impaired lower motor neuron function

Abstract: Spinal muscular atrophy (SMA) represents the second most common fatal autosomal recessive disorder after cystic fibrosis. Due to the high carrier frequency, the burden of this genetic disorder is very heavy in developing countries like India. The aim was to study the clinical and molecular characteristics of patients suspected with SMA. It was a cross sectional study of 105 cases from January 2008 to August 2012. Patients demographic and presenting features and PCR findings were noted. 65 (62%) cases had a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In index case, exons 7 and 8 of gene SMN1 and exon 7 of SMN2 genes were found to be deleted which is a rare phenomenon. This mutation is the most common type of mutation and one study conducted in Ahmadabad, Gujarat by Sheth et al [8] on 105 children showed that Werdnig Hoffman illness was the most prevalent variety, with 34 (52.3%) of the children having it. A similar case of Werdnig Hoffmann syndrome was also reported by Collado Ortiz MA et al (9) where a baby presented with respiratory problems and had tongue fasciculations classically, which was also seen in our index case too.…”
Section: Discussionmentioning
confidence: 99%
“…In index case, exons 7 and 8 of gene SMN1 and exon 7 of SMN2 genes were found to be deleted which is a rare phenomenon. This mutation is the most common type of mutation and one study conducted in Ahmadabad, Gujarat by Sheth et al [8] on 105 children showed that Werdnig Hoffman illness was the most prevalent variety, with 34 (52.3%) of the children having it. A similar case of Werdnig Hoffmann syndrome was also reported by Collado Ortiz MA et al (9) where a baby presented with respiratory problems and had tongue fasciculations classically, which was also seen in our index case too.…”
Section: Discussionmentioning
confidence: 99%
“…SMA is of three types and associated with homozygous deletion of survival motor neuron gene in 5q 13. [1,2] The childhood SMA are important cause of mortality and morbidity with incidence of 1in 6000-10000 live births. [3] SMA is classified into three types; in type 1 severe generalized hypotonia is present.…”
Section: Introduction: Discussionmentioning
confidence: 99%
“…Electromyography can be done but is generally not required when genetic studies are confirmatory. Various mutations have been defined in a study conducted in Ahmadabad, Gujarat by Sheth et al 4 from January 2008 to August 2012, where 105 patients were studied. A definite diagnosis of SMA was found in 65 (62%) of the patients.…”
mentioning
confidence: 99%